Gravity currents interacting with slopes and overhangs. (January 2023) - Maggi, M.R.; Adduce, C.; Lane-Serff, G.F.
Abstract: When a gravity current interacts with a barrier the flow is reflected back in the form of a moving hydraulic jump or bore. This latter phenomenon has important implications for estuarine mixing and sediment reworking in the oceanographic context. In order to examine those reflection processes two-dimensional gravity currents interacting with slopes and overhanging barriers are examined by laboratory experiments and theoretical analysis. Relevant parameters such as the initial volume of the dense fluid, the opening of the fixed gate used for the dense fluid release and the angle of the slope or overhang positioned inside the tank, were varied. An image analysis technique based on light attenuation was applied to evaluate the instantaneous density fields. The theoretical predictions, based on shallow-water theory, give reasonable agreement compared with the laboratory experiments about the spatial position of the dense current and the definition of the point where the reflection process starts. Moreover, the analysis of the density fields highlights the presence of areas within the dense current characterized by a greater dilution due to the reflection of the current. Nevertheless, the bulk entrainment parameter is only slightly affected by the presence of a steep slope or overhang. Highlights: Experimental study on gravity currents interacting with slopes and overhangs. The dynamics of the current is deeply affected by the interaction with the slopes and overhangs. Theoretical predictions agree well with the laboratory measurements. The entrainment is slightly affected by the presence of a steep slope or overhang.